Personality Traits in Marathon Runners and Sedentary Controls With MMPI-2-RF - Roeh, Astrid; Engel, Rolf R.; Lembeck, Moritz; Pross, Benjamin; Papazova, Irina; Schoenfeld, Julia; Halle, Martin; Falkai, Peter; Scherr, Johannes; Hasan, Alkomiet (Frontiers in Psychology, 2020)
Background Endurance exercise in general and marathon running in particular have become increasingly popular over the past decades. Recent investigations about personality structures in this cohort and comparisons to non-active cohorts are lacking. Methods In the ReCaP study (Running effects on Cognition and Plasticity), a total of 100 marathon runners and 46 sedentary controls were recruited. After elimination of Minnesota Multiphasic Personality Inventory 2 Restructured Form (MMPI-2-RF) profiles with insufficient validity, 79 marathon runners (MA) and 27 sedentary controls (SC) remained for final analyses. Depressive symptoms were evaluated with Beck Depression Inventory (BDI) and Hamilton Depression Scale (HAMD). Results MA had lower scores in scales measuring somatic and cognitive complaints, stress, demoralization, hopelessness and distrust. Within the marathon group, committed runners exhibited hypomanic traits compared to regular runners. Discussion and conclusion Personality differences could be summarized as (sub-)depressive personality traits in SC compared to MA rather than typical (sub-) depressive symptoms in the meaning of depressive disorders. Future studies should further evaluate cause and consequence of endurance training and hypomanic or euthymic symptoms, as a two-way interaction exists.